(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Agriculture is perhaps the most inclusive word used to cover various ways of providing food and other goods for the human population of crops and domestic animals. Agriculture in developing nations such as India prefers to utilize and attract women, but is not considered as employees/employed. This study focuses largely on the comparison of males and females in agriculture, such as statistics and table data representing the difference in the working of females and males for various decades in agriculture. This article also provides complete data about gender disparities in agriculture through resources (Labor market, land, education, and technology). As just a consequence of the globalization of commerce and agriculture, and modifications in national policies, the scope and possibilities of agro-based have considerably grown, resulting in an expansion in business in this sector. India’s fast-growing rural market is delighting the globe, which is vital for the corporate growth plan of the country.